(untitled) (Scientific journal of the Fergana State University, 2024)
This article shows the development of professional training of future teachers of military education based on the technological approach, their personal qualities, the essence of their level of knowledge, as well as the regular education and training of students and young people, and their constant improvement of the spirit of military patriotism. It is stated that the main goal of military education teachers is to successfully provide knowledge and education to students and to regularly develop their professional training. The article also emphasizes that the correct and effective organization of the computer-based teaching process ensures the guaranteed achievement of educational goals, and advanced teaching technologies will not be effective if the teaching process is not well organized. It is envisaged that these technologies will enable the simultaneous presentation of verbal and visual forms of educational information, and the adaptation of the teaching process to the goals. Observations show that the teacher participates as an organizer and manager of the process of knowledge acquisition, and the scientific-philosophical analysis of only correcting and controlling the formal skills of students when working with a computer is expressed.